Meningkatkan Pengetahuan Masyarakat Mengenai Balai Pemasyarakatan - Fathoni, Muhammad Rizal; Faradila, Widya; Chomah, Isti; Pangestu, Marliyoda Aji; Gemilang, Mohamad Ridho Pijar; Arrisandy, Muhammad Zahniar (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
This community service program was carried out in Gilingan Village, Surakarta, Central Java, Indonesia. related to aspects of community social services and analysis of social reintegration policies which focus on the "ecological" approach as a form of completing recovery for the implementation of Social Reintegration for correctional clients and also increasing the level of welfare of the community and families of correctional clients in villages and correctional institutions. This program is implemented using a social capital approach model with stages of observation and outreach to the community.